Temporary versus Permanent Shocks: Explaining Corporate Financial Policies - Gorbenko, Alexander S.; Strebulaev, Ilya A. (Review of Financial Studies, 2010)
We investigate corporate financial policies in the presence of both temporary and permanent shocks to firms’ cash flows. In our framework, cash flows can be negative and are imperfectly correlated with firm value, and earnings volatility differs from asset volatility. These results are consistent with empirical stylized facts. They are also contrary to the implications of existing dynamic capital structure models that allow only for permanent shocks to cash flows. Temporary shocks increase the importance of financial flexibility and may provide an intuitively simple and realistic explanation of empirically observed financial conservatism and low leverage phenomena. The theoretical framework developed in this article general enough to be used in various corporate finance applications.